Motivation, Critical Thinking and Academic Verification of High School Students Information-seeking Behavior - Hidayat, Z; Saefudin, Asep; Sumartono, Sumartono (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
High school students have known as Gen Y or Z and their media using can be understand on their information-seeking behavior. This researchâs purposes were: 1) to analyze the studentsâ motivation; 2) to analyze the critical thinking and academic verification; 3) to analyze the information-seeking behavior. This study used quantitative approach through survey among 1125 respondents in nine clusters, i.e. Central, East, North, West, and South of Jakarta, Tangerang, Bekasi, Depok, and Bogor. Schools sampling based on